2020
DOI: 10.15252/embr.202050845
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiration is required to provide amino acids during fermentative proliferation of fission yeast

Abstract: When glucose is available, many organisms repress mitochondrial respiration in favour of aerobic glycolysis, or fermentation in yeast, that suffices for ATP production. Fission yeast cells, however, rely partially on respiration for rapid proliferation under fermentative conditions. Here, we determined the limiting factors that require respiratory function during fermentation. When inhibiting the electron transport chain, supplementation with arginine was necessary and sufficient to restore rapid proliferation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 65 publications
(86 reference statements)
1
31
2
Order By: Relevance
“…We determined absolute concentrations of intracellular amino acids in nmol/6 × 10 7 cells ( Supplementary Table 1 ). The amino acid quantities, obtained from nondividing cells, differed from those previously reported for fission yeast which have been obtained from rapidly proliferating cells ( 20 , 24 ). At the onset of stationary phase, the total amino acid concentrations were lower in pka1Δ than in wild-type cells ( Figure 1B ).…”
Section: Resultscontrasting
confidence: 63%
“…We determined absolute concentrations of intracellular amino acids in nmol/6 × 10 7 cells ( Supplementary Table 1 ). The amino acid quantities, obtained from nondividing cells, differed from those previously reported for fission yeast which have been obtained from rapidly proliferating cells ( 20 , 24 ). At the onset of stationary phase, the total amino acid concentrations were lower in pka1Δ than in wild-type cells ( Figure 1B ).…”
Section: Resultscontrasting
confidence: 63%
“…In fact, glutamate is the most abundant free amino acid in E. coli [ 37 ]. The studies on eukaryotic cells have shown that rapid decreases of intracellular amino acids, especially glutamate, occurred when the ETC was inhibited [ 38 , 39 ]. Glutamate catabolism was mainly catalyzed by aspartate transaminase (AST), which converts glutamate to α-ketoglutarate (AKG) via transamination with oxaloacetate, producing aspartate [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all isolated mutants may lose mitotic competence during G0 phase, or alternatively, may lose the capacity to exit from G0 phase upon replenishment of nitrogen. It is not surprising that mitochondria become essential under nitrogen starvation, as amino acid metabolism is quite active in mitochondria and mitochondrial respiration is important for synthesis of certain amino acids, such as arginine [ 11 ]. However, since none of the defective genes examined in this study are directly related to nutrient recycling, and since during nitrogen-depleted G0 phase, amino acid levels are thought to be maintained by recycling rather than synthesis, further studies are required to understand the mechanisms underlying the nutritional phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the presence of a respiratory poison (antimycin A), S. pombe cells can grow and divide at a reduced rate, if glucose concentrations are higher than 0.2% [ 11 , 12 ]. Respiratory activity thus appears to be optional for cell proliferation under conditions in which an adequate concentration of glucose is present, while it is important for synthesis of amino acids derived from the Krebs cycle metabolite α-ketoglutarate [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation